Gene expression profiling indicates a shift in ammonia assimilation capacity along the hepatic acinus induced by different forms of selenium in vitamin–mineral mixes fed to beef steers grazing on toxic endophyte-infected tall fescue - Jia, Yang; Son, Kwangwon; Matthews, James C. (Frontiers in Animal Science, 2023)
Recently, we demonstrated that supplementing (with 3 mg Se per day) the diets of growing beef steers grazing on Se-deficient toxic endophyte-infected tall fescue-based forage with either organic Se (OSe, SEL-PLEX) or a 1:1 blend (MIX) of OSe and inorganic Se (ISe, sodium selenite) in vitamin–mineral mixes, rather than inorganic forms of Se, ameliorated several classic serum symptoms of fescue toxicosis. Importantly, higher levels of hepatic glutamine synthetase activity were observed in MIX and OSe steers. Accordingly, transcriptome level and targeted mRNA expression analyses were conducted on the same liver tissue to determine if Se treatments affected other hepatic metabolic pathways, especially those that are responsible for supplying substrates of glutamine synthetase. The effect of ISe, OSe, and MIX treatments (n = 8/treatment) on the relative abundances of mRNA [determined using microarray and real-time reverse-transcription PCR (RT-PCR)] and protein (determined using Western blotting) in liver tissue was assessed by ANOVA. Fisher’s protected LSD procedure was used to separate treatment means, with significance being declared at p ≤ 0.05. Microarray analysis identified (p< 0.01, false discovery rate of< 33%) 573 annotated differentially expressed gene (DEG) transcripts. Canonical pathway analysis identified the DEGs that are central to glutamine and glutamate biosynthesis/degradation and proline biosynthesis. Targeted RT-PCR analyses found that MIX and OSe steers had lower periportal ammonia-assimilation and urea-synthesizing capacities (lower glutaminase 2, key ornithine cycle enzymes, and mitochondrial ornithine/citrulline exchanger mRNA) than ISe steers. In addition, MIX and OSe steers had a higher capacity for pericentral ammonia assimilation (higher glutamine synthetase activity) and a higher capacity for the production of glutamate in pericentral hepatocytes from α-ketoglutarate (higher levels of glutamine dehydrogenase, and decreased levels of arginase 2 and ornithine aminotransferase and mRNA). The form of supplemental Se also affected steers’ capacity for hepatic proline metabolism, with OSe steers having a higher capacity for proline synthesis and MIX steers having a higher capacity for pyroline-5-carboxylate synthesis. In conclusion, supplementing the diets of growing beef steers grazing on toxic endophyte-infected tall fescue with MIX and OSe in vitamin–mineral mixes, rather than with inorganic forms of Se, shifts hepatic ammonia assimilation from periportal urea production to pericentral glutamine production, thus potentially increasing whole-animal N efficiency by increasing the supply of hepatic-synthesized glutamine.